Hubungan Budaya Dan Adat Istiadat Dengan Jumlah Kunjungan Antenatal Care (ANC) Di Wilayah Suku Baduy - Nurhayati , Titi; Yuliwati , Nanik (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: ANC is a stage of examination of pregnant women carried out by professional staff which is given to mothers during pregnancy which is carried out in accordance with predetermined standards in order to achieve quality services (Siregar et al., 2023). With ANC, it can be used as a forum by health workers to convey information about health to pregnant women better and can improve the quality of life for mothers and babies who are born later. Indirectly, ANC visits will have an impact on improving the quality of health services. Methods: The type of research used in this research is analytical observational with a cross sectional approach. The research was carried out in the Baduy tribe area, Kanekes Village. The total sample was 30 respondents. The sampling technique in this research is the side accidental technique. The instrument in this research is a questionnaire. The analytical method used is Chi-Square analysis. Results: The results of the analysis of the relationship between customs and ANC visits in the Baduy tribal area in 2023 from 30 respondents using the chi-square statistical test showed a p-value of 0.638 > 0.05. The results of the analysis of the relationship between culture and ANC visits in the Baduy tribe area in 2023 from 30 respondents using the chi-square statistical test showed a p-value of 0.004 < 0.05 Conclusion: There is no significant relationship between customs and the regularity of ANC visits and there is a significant relationship between culture and the regularity of ANC visits